Is Nitric Oxide (NO) the Last Word in Radiosensitization? A Review - Oronsky, Bryan T (Neoplasia Press Inc., 2012)
As a short-lived radical that diffuses across membranes, rather than interacting with membrane-bound receptors, nitric oxide (NO) represents a significant departure from synthetically derived radiosensitizers. An endogenous compound, NO may equal or surpass its molecular cousin, oxygen, as a hypoxic radiosensitizer, through pleiotropic phenotypic effects on tumor perfusion, cell signaling, mitochondrial respiration, the fixation of radiation-induced damage, and the radioprotection of normal tissue. However, unlike oxygen, in the context of radiosensitization, the clinical role and utility of NO are poorly understood, with often contradictory and controversial reported effects: whether NO functions as a radiosensitizer may ultimately be contextual to the tumor microenvironment. This may make NO manipulation an ideal candidate for a personalized radiosensitization approach tailored to specific patient and tumor types/microenvironmental characteristics. Effective delivery of NO both systemically and directly to the tumor may be critical to the success of this approach. Compounds that release NO or NO precursors have the potential to drive innovation and result in a new fertile branch of the radiosensitizer tree.